Seroprevalence of HIV antibodies and risk factors in healthy young males from upper north Thailand - Theetranont C. (2014)
In the Spring of 1991 a random sample of young men from Upper Northern Thailand (mean age = 21 years) was interviewed by trained medical students from Chiang Mai University, serum samples were obtained and analyzed for prevalence of HIV-1 antibodies and for syphilis, and risk factors for HIV infection were assessed. It was found that Commercial Sex Workers (CSW) were the principal risk factor, that consistent condom use is rare, and the rates of HIV infection are rising rapidly. Sociodemographic background, homosexual behavior, drug use, and history of STD's were found to be not significant risk factors. The conclusions are that the education campaigns should be intensified to reduce the frequency of contact with CSW and to encourage consistent use of condoms.